(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The purpose of applying the EIA, environmental impact assessment is to integrate development and environmental sustainability.EIA being a planning tool tries to identify a plan for environmental protection and enhancement on a project by project basis. It provides a plan that will minimize the adverse impacts of the proposed project. In the last two decades the concept of Sustainable development has gained vast international recognition. According to the World Commission on Environment and Development in 1987, (Brundtland Commission 1987) .Sustainable le development is defined as the development that meets the present need without compromising the future generation’s ability to fulfill their own wants. Public involvement is very essential in the process of EIA. The success rate of the EIA process increases by positive public involvement.